WORK-FAMILY CONFLICT AND COPING STRATEGIES IN UNMARRIED FEMALE TEACHERS' LIFE - Yusuf Hadi Putra, Muhammad (UIN Sunan Gunung Djati Bandung, 2024)
The aim of this study to explore conflict and coping strategies employed by unmarried female teachers to manage the demands of both work and personal life more effectively. Being a teacher is complex and it is more complex in women gender, especially in balancing professional duties and personal life, known as work-family conflict. In reality, this conflict is not exclusive to married women with families but also affects unmarried women. Greenhaus & Beutell (1985) defined the conflict based on three types, namely time-based conflict, strains-based conflict, and behaviour-based conflict. To deal with it, Stuart and Sundeen (1991) defined two types of coping mechanisms that individuals employ: problem-focused coping (direct action) and emotion-focused coping (palliative form). The study using a qualitative approach and phenomenological design to explore deeply regarding the phenomenon. Through qualitative interviews with four unmarried female teachers the findings reveal diverse perspectives on time-based, strain-based, and behavior-based conflicts. The participants articulate the time-based conflict arising from extended work hours, impacting the quality of family interactions. Strain-based conflict is illuminated through external impositions, continuous communication demands, conflicting family and work pressures, and the emotional toll of career decisions. Behavior-based conflict underscores the challenges of adapting behavior to meet divergent expectations, affecting emotional well-being and identity. In response to these conflicts, the coping strategies employed by the participants predominantly lean towards emotion-focused mechanisms. The implications of the research highlight the need for tailored interventions that recognize individual experiences and promote a harmonious integration of work and family roles. Recommendations include the development of workplace policies supporting work-life balance, training on adaptive behavior strategies, and fostering a supportive organizational culture. By addressing these findings, the research contributes to a deeper understanding of the complexities surrounding work-family conflict and coping mechanisms among unmarried female teachers..